A mathematical model for within-host Toxoplasma gondii invasion dynamics - Adam Sullivan; Folashade Agusto; Sharon Bewick; Chunlei Su; Suzanne Lenhart; Xiaopeng Zhao (Mathematical Biosciences and Engineering)
Toxoplasma gondii (T. gondii) is a protozoan parasite thatinfects a wide range of intermediate hosts, including all mammals and birds.Up to 20% of the human population in the US and 30% in the world arechronically infected. This paper presents a mathematical model to describeintra-host dynamics of T. gondii infection. The model considers theinvasion process, egress kinetics, interconversion between fast-replicatingtachyzoite stage and slowly replicating bradyzoite stage, as well as thehost's immune response. Analytical and numerical studies of the model can helpto understand the influences of various parameters to the transient andsteady-state dynamics of the disease infection.